Respiration, phytoplankton size and the metabolic balance in the Atlantic gyres - Serret, Pablo; Lozano, Jose; Harris, Carolyn B.; Lange, Priscila K.; Tarran, Glen A.; Tilstone, Gavin H.; Woodward, E. Malcolm S.; Zubkov, Mikhail V. (Frontiers in Marine Science, 2023)
The balance between plankton photosynthesis (GPP) and community respiration (CR) in the euphotic zone (net community production, NCP) is an essential driver of the biological carbon pump. Deficient datasets and a lack of knowledge of the mechanisms regulating CR cause poor empirical models and oversimplified parameterisations that maintain NCP as one important unknown for projections of the carbon pump. One unresolved issue is the unexpected lack of relationships between CR and the biomass or size-structure of the phytoplankton, which undermines the use of remotely sensed observations to predict NCP. Here we analyse the spatial variation of plankton metabolism, chlorophyll a concentration (Chla), pico-and nanophytoplankton abundance and size-fractionated primary production ( 14CPP) along a latitudinal (49ºN-46ºS) transect of 73 stations across the Atlantic Ocean (AMT-22 cruise). The use of depth-weighted rates (rates integrated to the depth of 0.1 % PAR, divided by the regionally varying depth of integration) markedly improved the depiction of latitudinal patterns and the significance of relationships, over volumetric or integrated rates. Depth-weighted CR showed clear and consistent latitudinal patterns with relevance for the distribution of NCP. Depth-weighted Chla and CR exhibited a significant relationship (CRZ=1.42ChlaZ-0.21, r2 =0.69, N=37, p<0.001) with potential for the difficult prediction of CR. A general ratio of 1.42 mmolO2 mgChla-1 d-1 and a threshold Chla for net heterotrophy of ca. 0.25 mgChla m-3 can be tentatively proposed for the Atlantic, although further analyses of spatial and seasonal variation are necessary. We observed unusually positive NCP rates in the central part of the N gyre, due to a marked decrease of CR in a patch of high Synechococcus spp. abundance and high 14CPP by large phytoplankton. However, no relationship was observed between size-fractionated 14CPP and CR or the GPP:CR ratio during the cruise, contradicting the hypothesis that food web functioning is determined by the phytoplankton size structure. Such independence, together with the persistence of distinct GPP:CR and 14CPP:NCP relationships in distinct biogeographic provinces suggest a resilience of trophic dynamics and the existence of alternative ecosystem states, whose implications for projections of the metabolic state of the ocean are discussed.